Spatio-temporal analysis of built-up area and land surface temperature in Surakarta using Landsat imageries - Vidya Nahdiyatul Fikriyah; Danardono Danardono; Muhammad Iqbal Taufiqurrahman Sunariya; Munawar Cholil; Tegar Abdul Hafid; Muhammad Islam Ismail (Center for Science and Technology, IAIN Surakarta, 2022)
The need for built-up areas continues to increase, along with the increasing population in the city of Surakarta and its surrounding. This condition affects the land surface temperature which then leads to the change in climatic conditions. The availability of land for settlement and surface temperature will affect the comfort level of living in a city. For this reason, this study aims to map the distribution of built-up area and the surface temperature of Surakarta city and discusses the relationship between these two aspects spatially and temporally. The data used are Landsat imageries recorded in 2000, 2013, and 2019. The built-up area was identified using Normalized Difference Built-Up Index (NDBI), while the temperature data was obtained through thermal band processing using Land Surface Temperature (LST) method. The results showed that during the period of the study, the built-up area and the surface temperature in Surakarta and its surroundings increased, especially in the eastern and southern parts of Surakarta. The results also showed that there is a positive correlation between the built-up index and its surface temperature.